2009
DOI: 10.3923/pjbs.2009.1330.1333
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Leptospirosis in Mazandaran Province, North of Iran: A One Year Survey

Abstract: The aim of this study was to provide the first report of incidence of leptospirosis and to determine the epidemiology of this zoonotic disease in Mazandaran Province, North of Iran. In the period of one year, from April 2007 to April 2008, forty seven confirmed reports of human cases of leptospirosis was received by Mazandaran Health Centre from local hospitals and leptospirosis laboratory. The annual incidence rate for the total population was 1.6 per 100,000 person-year. The majority of cases were males (84.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 11 publications
2
13
1
Order By: Relevance
“…This result is similar to findings in previous studies in Yemen among risk groups in Hodeida 3 which reported that higher prevalence of leptospirosis were in the 4 th and 5 th decades. Also the present results were similar with the results from the other parts of the world, in Iran, they confirmed that the highest seropositivity were present in aged range from 40-50 years 15 , but different from that in Chile, in which they show that the maximum rate of leptospirosis depend on antibodies result was in younger age (21-40 years) 16 , and in India the majority were obtained in the 35-44 years old 7 . These results can be explained with that the increasing of prevalence rate with increasing age could indicate an accumulation risk of infection over time.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This result is similar to findings in previous studies in Yemen among risk groups in Hodeida 3 which reported that higher prevalence of leptospirosis were in the 4 th and 5 th decades. Also the present results were similar with the results from the other parts of the world, in Iran, they confirmed that the highest seropositivity were present in aged range from 40-50 years 15 , but different from that in Chile, in which they show that the maximum rate of leptospirosis depend on antibodies result was in younger age (21-40 years) 16 , and in India the majority were obtained in the 35-44 years old 7 . These results can be explained with that the increasing of prevalence rate with increasing age could indicate an accumulation risk of infection over time.…”
Section: Discussionsupporting
confidence: 81%
“…Nevertheless, dissimilar findings were found among population at risk in Colombia as 19% 13 , in Tanzania: 15% 14 . Leptospirosis infection affects both adults and children everywhere 7,15,16 . When age of our slaughter house works and butchers was considered, the maximum rate of Leptospira IgG antibodies was found among older age group (median age >27 years) (50.9%) with associated OR equal to 3 (pv<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the more engagement of males to the agriculture, it is expected that the infection be higher among them. The mean age of the infected people in this study was 48.5 that is similar to some of the conducted study in north of Iran ( Esmaeili et al, 2009). This can be due to the sociological condition of our area that the elderly are more engaged in the agriculture, and the lower tendency of youths to this occupation caused the increase in the age average of the farmers.…”
Section: Discussionsupporting
confidence: 68%
“…The background of working in rice farm was the most common risk factor related to the infection. In other performed study in Mazandaran and Guilan province also, farmers were infected to this disease more than other occupations (Esmaeili et al, 2009;Mansour-Ghanaei et al, 2005). Due to the more engagement of males to the agriculture, it is expected that the infection be higher among them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation